2017
DOI: 10.1002/2327-6924.12463
|View full text |Cite
|
Sign up to set email alerts
|

Parental perception of child's body mass index and health within primary care

Abstract: Background and purpose Overweight and obesity are sensitive issues to address with pediatric patients during any visit. Patients and families may not recognize that their child is overweight or obese and may not be ready to make change. The goals for this study were to collect overall statistics on the clinic in regards to weight status of children presenting for well child visits and to capture parental perception of the child's weight status in relation to child's age. Methods A consecutive sample of parents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The aim of the current study was to examine the correctness of caregiver’s perception of their child’s diet quality and to investigate the potential factors that may influence this. To our knowledge, this is one of the first studies to pair caregivers with their child to examine caregiver’s perception of child diet quality, given that previous studies have focused on caregiver’s perception of their child’s weight status [ 21 , 22 , 23 , 24 ]. In the present study, our results showed that it is common for caregivers to be unable to identify the diet quality of their child.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of the current study was to examine the correctness of caregiver’s perception of their child’s diet quality and to investigate the potential factors that may influence this. To our knowledge, this is one of the first studies to pair caregivers with their child to examine caregiver’s perception of child diet quality, given that previous studies have focused on caregiver’s perception of their child’s weight status [ 21 , 22 , 23 , 24 ]. In the present study, our results showed that it is common for caregivers to be unable to identify the diet quality of their child.…”
Section: Discussionmentioning
confidence: 99%
“…Although not widely used, the effectiveness of CCDI has been proved in another study in children of the same age [ 14 ]. Finally, although caregivers’ perceptions of children’s diet quality were obtained by asking only one question, which may not be comprehensive, similar one question-based methods have been used previously in research relating to caregivers’ perception of children’s weight status [ 23 , 24 ]. Despite these limitations, this study is one of the first to examine caregiver’s perception of child diet quality and the factors that can influence this, and these results have highlighted the inadequate health awareness among parents or other caregivers and can provide direction for future health interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In any event, early assessments of a parent's perceptions of their child's weight, followed by regular follow up sessions, appropriate feedback, continuing education efforts, and efforts to chart the child's weight status over time, are likely to prove more helpful than not. 38,39 Highlighting this issue and its solutions in vulnerable communities, maternal health clinics, pediatrician offices and pre-school settings will likely be very helpful as well.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, the earlier parents are apprised of the importance of not under estimating their child's weight and are provided with supportive strategies to avoid this, the better the outlook for resolving the childhood obesity epidemic because regardless of culture and age, Reyes and Higgins 39 found that the younger the child is, the more likely it is that the parent will underestimate their weight status. To intervene on this problem, they suggest clinicians engage in early discussions that focus on what a healthy weight is and how having a healthy weight can predict future health.…”
Section: Discussionmentioning
confidence: 99%